A Study on the Design and Application of a Home-School Collaborative Progress Tracking System for Special Children’s Rehabilitation - Xu, Ting (Research and Advances in Education, 2025)
This study addresses the persistent “5+2=0” dilemma in special children’s rehabilitation, wherein over 30% of the gains from five days of school-based intervention are nullified by two-day gaps in home environments. Drawing upon fifteen years of frontline teaching and competition experience, coupled with AMI Montessori observational methods and formative assessment theory from Loyola University, the researcher developed the “Xu Ting Rehabilitation Data Assessment Index.” This index, embedded within a home-school collaborative rehabilitation progress tracking system, comprises 32 tertiary behavioral anchors and employs a hybrid data collection mode combining Likert scales with 15-second video clips, enabling automatic validation of data authenticity in home settings. An 18-month quasi-experimental study conducted across four special schools in Wuhan involved 120 children with autism, intellectual disabilities, and speech-language disorders aged 3 to 8, randomly assigned to experimental and control groups. Results demonstrated that the experimental group’s home rehabilitation completion rate increased from a baseline of 45% to a stable 80.2%, significantly exceeding the control group’s 47.5%. In the “social reciprocity” domain, rehabilitation progress accelerated by 0.85 standard deviations compared to the control group. Teachers’ average daily data processing time decreased from 47 minutes to 19 minutes, while home-school communication frequency rose from 3.1 to 12.3 monthly interactions (Bornman, J., 2004). Qualitative analysis revealed a fundamental shift in parental roles from “passive implementers” to “observant reflectors,” with teachers’ decision-making patterns transitioning from “experience-driven” to “data-driven.” The study also identified challenges including privacy concerns, intergenerational digital divides, and the need for sustained professional support for teacher role transformation. This research provides a quantifiable, replicable digital solution to address data discontinuities and the “last-mile” problem of professional guidance in home-school collaboration, bridges theoretical gaps in localizing Montessori observation science, and offers practical guidance for optimizing special education resource allocation in central China.